1978
DOI: 10.1111/j.1752-7325.1978.tb03712.x
|View full text |Cite
|
Sign up to set email alerts
|

DENTISTS’PERCEPTIONS OF THEIR PATIENTS: RELATION TO QUALITY OF CARE #

Abstract: This study investigates dentists' perceptions of their patients and the relation of these perceptions to measures of actual quality of restorative treatment. The results indicate that 1) though the dentists see their patients as "cooperative," they perceived a substantial number of "problems," i.e., willingness to pay for optimal care or follow professional recommendations; and 2) there are significant associations between dentists' perceptions of patients and measures of the quality of restorative treatments;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

1984
1984
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 30 publications
1
8
0
2
Order By: Relevance
“…In this study, participants described some patients as being too ‘unreliable’ to benefit from preventive care. This is consistent with previous research that shows that dentists may find it difficult to treat patients who do not value oral health, are disinterested or ‘uncooperative’ , providing them with a different quality of dental care . This study provides evidence that this is particularly salient to how dentists’ approach prevention – that their deeply‐held beliefs about the motivation, values or cooperativeness of patients may be an important explanatory factor in determining whether or not prevention is offered.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, participants described some patients as being too ‘unreliable’ to benefit from preventive care. This is consistent with previous research that shows that dentists may find it difficult to treat patients who do not value oral health, are disinterested or ‘uncooperative’ , providing them with a different quality of dental care . This study provides evidence that this is particularly salient to how dentists’ approach prevention – that their deeply‐held beliefs about the motivation, values or cooperativeness of patients may be an important explanatory factor in determining whether or not prevention is offered.…”
Section: Discussionsupporting
confidence: 89%
“…Oral health variables were recorded to indicate the status of each patient at the beginning of the current visit. A rating of these patients in terms of dental knowledge and payment factors also was recorded using a five-point Likert scale of items related to patient dental values (24,25). Residential postal code was also recorded for each patient treated and used to link with an areabased indicator of SES derived from census data (26).…”
Section: Methodsmentioning
confidence: 99%
“…This pessimistic view of patient compliance is in keeping with previous reports that patients fail to comply with dentists' recommendations 8 and that they are poorly motivated in following instructions concerning oral hygiene. [9][10][11] Bending and splaying of bristles was selected as the main indicator that a toothbrush should be renewed and confirms the findings of previous surveys of dentists 3,12 and patients. [13][14][15] Although one investigation reported the amount of toothbrush wear correlated with the length of time in use, 16 other studies found toothbrush wear varies among people and depends mainly on how the toothbrush is used.…”
Section: O N T H S R E C O M M E N D a T Io N S F O R P A T Ie N T Smentioning
confidence: 66%